Fetal Anthropometric Features: A Postmortem Study of Fetuses After the Termination of Pregnancy for Psychosocial Reasons Between 12 and 20 Gestational Weeks. (May 2019) - Muller Brochut, Anne-Claude; Taffe, Patrick; Piaget-Rossel, Romain; de Leval, Laurence; Rougemont, Anne-Laure
Introduction: Reference ranges in fetal postmortem anthropometric data derive from heterogeneous studies and rely on data obtained after intrauterine fetal death and abortion, which may introduce bias in the reported fetal growth parameters. We report anthropometric findings in fetuses with the least variation due to cause of death or developmental anomalies. Methods: We analyzed fetuses after the termination of pregnancy for psychosocial reasons. The external measurements, X-ray dimensions, and body and organ weights were recorded as well as the placenta weight. A thorough and standardized postmortem analysis allowed the design of 2 different groups. Group 1 was composed of fetuses (1) born to mothers with no relevant obstetrical history, (2) no X-ray anomaly, (3) no abnormal autopsy findings, and (4) unremarkable placenta histology. An anomaly in any of these 4 entities moved the fetuses to Group 2. For reference ranges and graph construction, a well-designed statistical methodology was applied. Results: A total of 335 fetuses were analyzed during an 11-year period. Group 1 comprised 232 fetuses aged 12 to 20 gestational weeks, whereas 103 fetuses were considered in Group 2. Comparison between the 2 groups showed almost no differences. Only the Group 1 results were submitted to statistical analysis, and reference ranges and graphs were constructed. Conclusions: To the best of our knowledge, we provide in this study the first anthropometric references established from almost normal fetuses, albeit for a limited fetal timeframe.